2015
DOI: 10.4209/aaqr.2015.04.0236
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Nanoparticles from Air Using Melt-Blown Filtering Media

Abstract: Over the last few years, expectations have grown for the development of appropriate materials for separation of nanoparticles of different morphologies from air. Therefore, the objective of this work was to conduct a broad study of the process of filtration of polydisperse nanoaerosols in materials of our design and production. They were made using the modified melt-blown technology, a very promising technique that allows to produce large amounts of fibers with a wide range of diameters which when properly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…This was mainly because with additional increment from 10 to 20 wt.% in TPU content caused a slight decrement in mean fiber diameter during the high‐speed hot air stretching process 24 . Moreover, the visual inspection indicates that the addition of a higher amount of TPU (20 wt.%) decreases the melt viscosity of the 80PP‐20TPU blend polymer 25 . The decrement in melt viscosity could also be related to the incorporation of PP‐G‐mA.…”
Section: Resultsmentioning
confidence: 96%
“…This was mainly because with additional increment from 10 to 20 wt.% in TPU content caused a slight decrement in mean fiber diameter during the high‐speed hot air stretching process 24 . Moreover, the visual inspection indicates that the addition of a higher amount of TPU (20 wt.%) decreases the melt viscosity of the 80PP‐20TPU blend polymer 25 . The decrement in melt viscosity could also be related to the incorporation of PP‐G‐mA.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, the melt blowing process creates nonwoven fibers with characteristics such as low abrasion resistance (Dutton 2008) and improved efficiency of the MB filter media (Podg orski et al 2006;Jackiewicz et al 2013). Jackiewicz and Werner (2015) demonstrated that nanofiber filters are effective for nanoparticle removal. They produced polypropylene fibrous filters (i.e., filter mats) with diameters of 0.47-9.62 mm using a modified MB technique in which it was possible to increase the efficiency of the separation of both solid and liquid nanoparticles from air with a higher pressure drop (Jackiewicz and Werner 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Jackiewicz and Werner (2015) demonstrated that nanofiber filters are effective for nanoparticle removal. They produced polypropylene fibrous filters (i.e., filter mats) with diameters of 0.47-9.62 mm using a modified MB technique in which it was possible to increase the efficiency of the separation of both solid and liquid nanoparticles from air with a higher pressure drop (Jackiewicz and Werner 2015). In another application, a modified MB filter media were also effective for improving the efficiency of respiratory protective devices against nanoparticles (Brochocka et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of A2–C2 samples, the base material of non-woven PP-based fibrous mats was manufactured using melt-blown technology [ 42 ]. As a result, 50-layer filter mats (2.86 mm thick) were trimmed into circles with an effective diameter of 15 cm.…”
Section: Methodsmentioning
confidence: 99%